Mencermati Era Digital dalam Organisasi - Hari Mantik (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2016)
Creating an organization in the information age is not as simple as we imagine. Not only from the perspective of the level of complexity of the organization itself, but how an organization can and dare to make a breakthrough began with the adoption, integration and approaches to current technologies is an added value and the key to the development of the organization itself. It should be noted how the stability of a neighborhood phenomenon, the phenomenon of globalization, and the acceleration of technological advances that directly and indirectly affect the wheels of the organization who would not want to have to deal with information technology base.